Cutaneous and splenic mastocytosis in a juvenile Malayan tiger. (March 2022) - Smedley, Rebecca C.; Stedman, Nancy L.; Kiupel, Matti
A male Malayan tiger cub developed well-circumscribed, erythematous, alopecic lesions on the face, torso, and paws when 1-wk-old. Biopsies of a torso lesion and a right front paw lesion at 1-mo-old confirmed cutaneous mast cell tumors (MCTs). MCTs on the paws grew into pendulous masses up to 6.5 cm in diameter by 3-mo-old, but those on the face and torso regressed. Fine-needle aspiration of the spleen at 3-mo-old revealed marked mast cell infiltration. The spleen and the right paw cutaneous MCT were removed; the paw MCT recurred within 7 d. A 12-bp tandem duplication, suggesting a somatic mutation, was identified in exon 8 of c-KIT in DNA extracted from the cutaneous MCT on the right paw and from one over the torso, but not from the spleen. Remaining MCTs on the paws regressed slowly following splenectomy and had completely regressed by 1-y-old. At 7-y-old, there was no recurrence of any mast cell disease. Mast cell disease in this tiger cub is similar to a report in a domestic kitten and to pediatric mastocytosis in humans, which commonly begins in infancy, improves by adolescence, and is associated with somatic c-kit mutations. To our knowledge, mastocytosis has not been reported previously in a juvenile exotic felid.